Rapid eye movements sleep as a predictor of functional outcome after stroke: a translational study. Issue 10 (19th July 2018) - Pace, Marta; Camilo, Millene R; Seiler, Andrea; Duss, Simone B; Mathis, Johannes; Manconi, Mauro; Bassetti, Claudio L
Abstract: Study Objectives: Sleep disturbances are common in acute stroke patients and are linked with a negative stroke outcome. However, it is also unclear which and how such changes may be related to stroke outcome. To explore this link, we performed a sleep electroencephalogram (EEG) study in animals and humans after ischemic stroke. Methods: (1) Animal study: 12 male rats were assigned to two groups: ischemia (IS) and sham surgery (Sham). In both groups, sleep architecture was investigated 24 h before surgery and for the following 3 days. (2) Human study: 153 patients with ischemic stroke participating in the SAS-CARE prospective, multicenter cohort study had a polysomnography within 9 days after stroke onset. Functional stroke outcome was assessed by the modified Rankin Scale (mRS) at hospital discharge (short-term outcome) and at a 3-month follow-up (long-term outcome). Results: (1) Animal study: rapid eye movement (REM) sleep was significantly reduced in the IS group compared to the Sham group. (2) Human study: patients with poor short-term functional outcome had a reduction of REM sleep and prolonged REM latency during the acute phase of stroke. REM latency was the only sleep EEG variable found to be significantly related to short- and long-term functional impairment in a multiple linear regression analysis. Conclusions: Acute ischemic stroke is followed by a significant reduction of REM sleep in animals and humans. In humans, this reduction was linked with a bad stroke outcome; in addition, REM latency was found to be an independent predictor of stroke evolution. Potential explanations for this role of REM sleep in stroke are discussed. Clinical Trial Registration: http://clinicaltrials.gov . Unique identifier: NCT01097967